ANALISIS FRAMING TENTANG PERUBAHAN IKLIM PADA TAYANGAN YOUTUBE NAJWA SHIHAB "2050, ANDAI KITA TIDAK MELAKUKAN APA-APA" - Ghina Kayla Namira (2024)
The show "2050, What If We Do Nothing" on Najwa Shihab's Youtube channel packages the topic of climate change in an insightfully narrated 4 minutes and 57 seconds length video. Media has the power to construct reality. The power of media to construct a reality intertwines with the role of framing in enabling a social movement, particularly concerning climate change. The objective of this research is to analyze how the framing of the show "2050, What If We Do Nothing" on addressing the climate change topic. The methodology of this research is a qualitative approach using the framing analysis model by Gamson and Modigliani. The findings of this study indicate that the condensing symbols in the show "2050, What If We Do Nothing" focus on the core frame, which is emphasizing that climate change poses a threat to the world and must be addressed urgently.